PSIKOEDUKASI POLA ASUH POSITIF UNTUK MENGURANGI PERILAKU KENAKALAN REMAJA DI DESA KARANGREJA - Rahma, Annisa Dwi; Dian Iva Prestiana, Novita; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2023)
Children and teenagers often engage in delinquent behavior at their age. However, this can still be avoided and even reduced this behavior. Parenting style is the first education that parents give to children, how they can provide positive parenting so as to create a child's character with positive behavior. If children have positive behavior, they will be able to have good social relationships. The parenting style provided focuses on democratic parenting. The aim of this activity is to provide several ways of good parenting to reduce juvenile delinquent behavior. The method used is psychoeducation by presenting material regarding positive parenting patterns and supported by image media and sharing sessions. The results of this activity show that there has been a change in parents' parenting patterns towards their children, parents have started to try to implement democratic parenting patterns, although it is not yet significant.